Plasticity over a wide range of strain rates and temperatures - Bodner, S.R. (Archives of Mechanics, 2005)
A number of constitutive theories of elastic-viscoplastic deformation were proposed over the past years which have been found useful for practical applications. Most of them use the second invariant of deviatoric stress, as identified by Huber, as the effective stress driving inelastic deformations. This paper examines a particular constitutive theory, that of Bodner-Partom, over a very wide range of strain rates and temperatures.